PERANAN SALES SECRETARY DALAM MENDUKUNG KELANCARAN MANAJEMEN SALES DI KUTA PARADISO HOTEL - Ni Luh Supartini; Cendana Cahyani Lestari Guyana (Institut Pariwisata dan Bisnis Internasional, 2020)
The role of a secretary is required in assiting to complete the whole works. As a secretary, the most important skill is managing time and choosing work priorities so that the main work can be completed on time. At the same time, there are a number of jobs beside of the main jobs should be completed. It affects the load of secretary’s jobs were fulled. This study aims to find out how the roles and responsibilities of the sales secretary who are concurrently as sales admins, as well as what are the obstacles faced in carrying out the tasks. Data was collected through observation, interview and documentation techniques. The data analysis technique used in this research is descriptive qualitative. The results of the study showed descriptively that the sales secretary is very instrumental in supporting the management system of sales at Kuta Paradiso Hotel, Bali. The problems was encountered by a secretary was lack of communication skills, lack of human resources that affect the load of secretry’s responsibilities was over.